Modulating intrinsic anomalous Hall effect in Fe3GeTe2 monolayer via strain engineering - Min Guo; Ju Zhou; Hai-Shuang Lu; Sheng Ju; Tian-Yi Cai (AIP Advances, 2023)
The Fe3GeTe2 monolayer, a ferromagnetic topological candidate with a high Curie temperature of 130 K, has recently garnered considerable interest. We investigated the impact of strain on the electronic, magnetic, and topological properties of the Fe3GeTe2 monolayer using density functional theory calculations. Our results showed that the Fe3GeTe2 monolayer was an itinerant ferromagnet with a high spin polarization of 69.93% and out-of-plane easy magnetization. Tensile strain had no profound impact on the anomalous Hall conductivity (AHC). However, when applying a compressive biaxial strain of −3%, the AHC at the Fermi level was dramatically enhanced to 1.62 e2/h, which is much larger than that of the bulk (0.7 e2/h) and bilayer (1.5 e2/h) material. The large AHC nearly coincided with the singularity of the energy bands near the M point. Our results highlight the potential of using strain engineering to control and optimize the properties of two-dimensional topological materials.